A new diagnostic character in the roots of the genus Grammosciadium DC. (Apiaceae) - Ulusoy, Fatma; Karakaya, Muhammet Ali̇; Mavi̇ İdman, Dudu Özlem; Bani̇, Bariş (Phytotaxa, 2017)
This study focuses on the root anatomical characteristics of the taxa of the genus Grammosciadium. Samples collected from plants gathered in 41 different localities in Turkey were studied. The results show that the general structure of the roots includes protective tissue (periderm), cortex and vascular tissue respectively from the outermost layer. The roots of G. subg. Grammosciadium include regularly arranged fibres within the protective tissue. Moreover, the existence, arrangement and density of the polyhedral sclereids just under the phellogen of the roots of G. subg. Caropodium reveal as remarkable characters. Among them, the density of all these sclerenchymatous layers is a diagnostic character for the taxa of the genus. This study remarks the importance of root anatomical characters in taxonomy of Grammosciadium.